Greek Debt Crisis "An Introduction to the Economic Effects of Austerity" - Panagiotis Mantalos (Örebro University School of Business, 2015)
We trace the reasons for the negative development of Greek government debt from 1980 to 2014 by studying the deficits of the Greek state under the same period. We also see the Greek debt under the different political regimes. We briefly describe the two bailout programs for Greece and finally we name the amount and Euro states that own the Greek loans. The negative effects of austerity are about 22% less GDP and total household and government consumption and monthly wages; finally, the unemployment rate grew 21%.
Keywords: C22; E62; F33; H63; O40; 330; Austerity; Consumption; Deficit; Greek Debt Crisis; GDP; Unemployment